Dissipative advertising signals quality even without repeat purchases - Laurent Linnemer (Center for Economic Studies and ifo Institute (CESifo), 2008)
Economists have emphasized the role of dissipative advertising and price as signals of quality. Most works, however, limit the number of types to two options: high and low quality. Yet, production costs and quality both result from R&D efforts and therefore are both uncertain. I characterize the optimal separating marketing mix (price and advertising) when quality and marginal cost are both subject to chance. In a static framework (no repeat purchases and no informed consumers), advertising appears to be necessary together with price to signal quality. Equilibrium profits depend on cost but not on quality: all rents are dissipated for signaling purpose.
Keywords: L12; L15; M37; 330; quality; signaling; dissipative advertising; Produktqualität; Signalling; Werbung; Betriebliche Preispolitik; Monopol; Gewinn; Theorie